2023
DOI: 10.1038/s41598-023-35744-x
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning based estimation of dynamic balance and gait adaptability in persons with neurological diseases using inertial sensors

Abstract: Poor dynamic balance and impaired gait adaptation to different contexts are hallmarks of people with neurological disorders (PwND), leading to difficulties in daily life and increased fall risk. Frequent assessment of dynamic balance and gait adaptability is therefore essential for monitoring the evolution of these impairments and/or the long-term effects of rehabilitation. The modified dynamic gait index (mDGI) is a validated clinical test specifically devoted to evaluating gait facets in clinical settings un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 81 publications
1
6
2
Order By: Relevance
“…Unexpectedly, Lyapunov exponents (LyE) did not show significant correlations with any clinical evaluations, including balance measures (i.e., PIGD and TUG). This is in contrast with previous results on a group of people with PD, multiple sclerosis and stroke showing a significant association between increasing LyE Step AP and decreased balance as measured by the mDGI [ 70 ]. This can be due to the fact that our sample was composed of persons with PD who showed less severe walking impairment, as suggested by the 6MWT distance which was significantly higher (+156 m) compared to that characterizing the PD group tested by Liuzzi et al [ 70 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, Lyapunov exponents (LyE) did not show significant correlations with any clinical evaluations, including balance measures (i.e., PIGD and TUG). This is in contrast with previous results on a group of people with PD, multiple sclerosis and stroke showing a significant association between increasing LyE Step AP and decreased balance as measured by the mDGI [ 70 ]. This can be due to the fact that our sample was composed of persons with PD who showed less severe walking impairment, as suggested by the 6MWT distance which was significantly higher (+156 m) compared to that characterizing the PD group tested by Liuzzi et al [ 70 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast with previous results on a group of people with PD, multiple sclerosis and stroke showing a significant association between increasing LyE Step AP and decreased balance as measured by the mDGI [ 70 ]. This can be due to the fact that our sample was composed of persons with PD who showed less severe walking impairment, as suggested by the 6MWT distance which was significantly higher (+156 m) compared to that characterizing the PD group tested by Liuzzi et al [ 70 ]. Another possible explanation could be that, in the present study, LyE was computed over the duration of one step and stride.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that a type of neural network was the best to recognize neurological patients, based on EMG data, allowing a classification accuracy of 80 to 90%, even in small samples. Similarly, Liuzzi et al [71] provided an estimation using ML to detect important information on dynamic balance and gait adaptability in ND to aid clinicians to identify clinical features that need to be improved in the rehabilitation setting.…”
Section: Future Directions Of Gait Analysismentioning
confidence: 99%
“…www.e-arm.org Similarly, sensor data during walking have been combined with clinical information to estimate dynamic balance ability in individuals with stroke, multiple sclerosis, and Parkinson's disease [36]. In the upper limb, IMUs have shown promise in assessing motor deficits in stroke and traumatic brain injury during the Wolf Motor Function Test [37], or evaluating tremor and bradykinesia for individuals with Parkinson's disease [38,39].…”
Section: Wearable Sensorsmentioning
confidence: 99%